Nonlinear Effects of Dynamic Export Pricing on Export Sales: A Longitudinal Investigation. Issue 3 (September 2019) - Chen, Jieke; Sousa, Carlos M.P.; He, Xinming
Little is known in the literature about dynamic export pricing, and particularly how the external environment interacts with a firm's export pricing decisions and its long-term effect on export sales. Therefore, this study develops a longitudinal framework to examine the quadratic effect of dynamic export pricing and its interaction with customer/competitive turbulence on export sales. By employing product-level longitudinal data, the authors also estimate the lagged effect from past dynamic export pricing and export sales while simultaneously controlling for endogeneity and unknown firm heterogeneity. The results indicate that dynamic export pricing appears to have inverted quadratic effects on export sales; this quadratic relationship is moderated by customer turbulence and competitive turbulence. The authors also focus on the changes of the curve and shifts of the turning point and delineate the fit lines that pinpoint the optimal dynamic export pricing in different export markets. Finally, previous actions and outcomes significantly influence the following year's export sales, which explains the long-term relationships.